“Dot in Circle” sign — a unique attribute of mycetoma foot on MRI: a report of two cases - A Aggarwal; M Gupta; B N Patel; S B Patel (Journal of Integrated Health Sciences)
Mycetoma or Madura Foot is a chronic localized granulomatous disease characterized by exuberant granulomatous tissue formation involving the subcutaneous plane. It is most common in tropical countries. Diagnosis has been traditionally done by microbiological culture and histopathological tissue diagnosis but these are often difficult to obtain and frequently inconclusive. MRI has recently emerged as a promising technique for early and prompt diagnosis of Mycetoma with the description of a highly specific sign called as “Dot in Circle” sign. We hereby present 2 cases showing this characteristic “Dot in circle” sign on MRI and thereby establishing the diagnosis of Madura Foot.